The Contribution of Frank Moore Cross to the Study of the Religion of Israel - Hackett, Jo Ann (Bulletin of ASOR, 2014)
Frank Cross was well known, of course, as a scholar of the Dead Sea Scrolls and of epigraphy generally, of the Deuteronomistic history, of historical and comparative linguistics, of textual criticism, but his contributions to our understanding of the religions of Israel and its surrounding nations are often overlooked. One reason is that his understanding of these cultures was complex and erudite, not written for the casual or even casually trained scholar. Another, possibly more operative reason, however, is that Cross's sense of the interrelationships among the religious traditions we know from Israel, Ugarit, the Phoenicians, and others was set forth so confidently and supported so richly that it has been taken as a given by many in our field who no longer realize that it is not an obvious scheme, that someone had to construct it. This paper will point to several of Cross's proposals that have changed the way we look at the religions of the Levant.